2008
DOI: 10.1002/prca.200780065
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐1‐antitrypsin and complement component C7 are involved in asthma exacerbation

Abstract: Asthma is the most common chronic disorder in childhood and asthma exacerbation is an important cause of childhood morbidity and hospitalization. Allergic responses are known to be biased toward T-helper type 2 in asthmatics; however, the pathogenesis of asthma is not simple, and our understanding of the disease mechanism remains incomplete. The aim of the present study was to identify protein expression signatures that reflect acute exacerbation of asthma. Plasma was taken twice from pediatric asthmatic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…These excised gels were destained with destaining solution containing 15 mmol/L potassium hexacyanoferrate (III) (Wako, Osaka, Japan) and 50 mmol/L sodium thiosulfate (Sigma, St Louis, Mo) and digested with sequencing-grade modified trypsin (Promega, Madison, Wis), and using these peptide extracts, we performed nano-HPLC sample separation with a Paradigm MS4 LC system (Michrom BioResources, Auburn, Calif) 14 and MALDI-TOF/TOF mass spectrometry with ultraflex II (BRUKER Daltonics, Billerica, Mass). 13 Molecular mass information obtained by MALDI-TOF/ TOF mass spectrometry was searched against the Swiss-Prot protein database (version 56.5, http://www.expasy.org/sprot/) with the MASCOT search program (version 2.2; MatrixScience, Boston, Mass) automatically using the Warp-LC software (BURUKER Daltnics), which attached to the ultraflex II. The following search criteria were used: (1) the taxonomy was Homo sapiens (human being); (2) the specified enzyme was trypsin, with up to 1 missed cleavage permitted; (3) the fixed modifications were carbamidomethylation of cysteine residues and variable modifications were oxidation of methionine residues; and (4) the peptide tolerance and MS/MS tolerance were set at 100 ppm and 6 0.5 d, respectively.…”
Section: Protein Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…These excised gels were destained with destaining solution containing 15 mmol/L potassium hexacyanoferrate (III) (Wako, Osaka, Japan) and 50 mmol/L sodium thiosulfate (Sigma, St Louis, Mo) and digested with sequencing-grade modified trypsin (Promega, Madison, Wis), and using these peptide extracts, we performed nano-HPLC sample separation with a Paradigm MS4 LC system (Michrom BioResources, Auburn, Calif) 14 and MALDI-TOF/TOF mass spectrometry with ultraflex II (BRUKER Daltonics, Billerica, Mass). 13 Molecular mass information obtained by MALDI-TOF/ TOF mass spectrometry was searched against the Swiss-Prot protein database (version 56.5, http://www.expasy.org/sprot/) with the MASCOT search program (version 2.2; MatrixScience, Boston, Mass) automatically using the Warp-LC software (BURUKER Daltnics), which attached to the ultraflex II. The following search criteria were used: (1) the taxonomy was Homo sapiens (human being); (2) the specified enzyme was trypsin, with up to 1 missed cleavage permitted; (3) the fixed modifications were carbamidomethylation of cysteine residues and variable modifications were oxidation of methionine residues; and (4) the peptide tolerance and MS/MS tolerance were set at 100 ppm and 6 0.5 d, respectively.…”
Section: Protein Identificationmentioning
confidence: 99%
“…13 Labeled proteins were visualized with a Typhoon 9400 Imager (GE Healthcare), and 24 images of paired samples were analyzed with the DeCyder Software Platform version 4.0 (GE Healthcare). The detailed Methods are available in this article's Online Repository at www.jacionline.org.…”
Section: Two-dimensional Polyacrylamide Gel Electrophoresis and Protementioning
confidence: 99%
“…A recent proteomic study has also shown that levels of haptoglobin are elevated in BAL fluid in patients with mild asthma, and reported that haptoglobin may play a role in the differentiation of fibroblast progenitor cells, suggesting a novel role for haptoglobin in airway remodeling in patients with asthma [20]. Conversely Nishioka et al showed that the serum concentration of haptoglobin was decreased during acute exacerbation in asthmatic children [21]. Haptoglobin isoforms and fragments are also elevated in plasma of severe acute respiratory syndrome (SARS) patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular weight (MW) and pI are theoretical and * indicates proteins present on the gel at a MW or pI different to these values novel role for haptoglobin in airway remodeling in patients with asthma [20]. Conversely Nishioka et al showed that the serum concentration of haptoglobin was decreased during acute exacerbation in asthmatic children [21]. Haptoglobin isoforms and fragments are also elevated in plasma of severe acute respiratory syndrome (SARS) patients [22].…”
Section: Discussionmentioning
confidence: 99%